Informational Mismatches: A Neglected Threat of Climate Change to Interspecific Interactions - Parejo, Deseada (Frontiers in Ecology and Evolution, 2016)
Interspecific interactions are deeply affected by the current scenario of climate change. This is because interactions are sensitive to many traits of interacting species as phenology, distribution, behaviour and relative abundances which may be differently influenced by climate change in each species. In this scenario, positive interactions, which require temporal coordination of events of life history of interacting species, could be particularly altered due to differential effects of climate change on phenology, apart from by the effects on abundance and distribution. Hitherto, studies focusing on the effects of climate change on positive biotic interactions are scarce and mainly focused on plant-pollinator interactions. Here I propose that, by inducing informational mismatches, climate change may lead to individuals from competing species relying on heterospecific social information to making mis- or un-informed decisions. The idea is that competing species are valuable sources of social information to each other provided overlap of their activities occurs. However, whenever coordination of events fails, competing species will co-occur at the wrong moment, co-occur only in small numbers or even not co-occur at all and thus they will not be able to access useful or any social information from heterospecifics. In that scenario, interacting species would be mis- or un- informed, and, consequently, decision taking will be impaired, leading to disequilibrium in the community. Throughout the manuscript, I will develop the idea of mismatches of information and illustrate it with some case studies.